Intercanthal Width of Bangladeshi Medical Students – A Photo-Anthropometric Study - Uddin, Sk Amin Mohi; Naushaba, Humaira; Paul, Uttam Kumar; Islam, AHM Mazharul; Jahan, Afroz; Akter, Tahmina; Urmi, Tamanna Mahmud (Bangladesh Journal of Anatomy, 2020)
Background: Intercanthal width, the distance from the inner canthus (endocanthion) of right eye to the inner canthus (endocanthion) of left eye, helps to identify race, age & gender of an individual. It is an essential guide to reconstructive surgery like ocular prosthetics, blepharoplasty and ptosis correction. It is also useful for evaluation of various dysmorphic syndromes. Objectives: Many studies were carried out in various populations to determine normative values of intercanthal width. However, there is no published article on this topic in Bangladesh. So, this study was aimed to measure the intercanthal width among the medical students of Bangladesh and to find out the variations in intercanthal width between male and female medical students. Materials and Methods: This cross sectional analytical study was carried out in the Department of Anatomy, Sir Salimullah Medical College, Dhaka from July 2017 to June 2018. Digital photographs of face in frontal view both in opened and closed eyes of the study subjects were taken from 200 consented medical students (100 male and 100 female) aged between 20 to 25 years. The actual “nose height” of the study subjects was measured from nasion to subnasale by slide caliper. Then the “nose height” of individual photograph was transformed into physically measured value by using transform option of Adobe Photoshop version : CC 2014 and ultimately photograph of eye was converted into actual size. Then the intercanthal width was measured from photograph by MB ruler software. Results: The mean ± SD of intercanthal width was 30.28±3.16 mm (range 22.22 - 39.97 mm) in male and 28.36±3.38 mm (range 17.26 - 36.81 mm) in female. Intercanthal width is significantly higher in male than female (P < 0.01). Conclusion: Intercanthal width shows sexual dimorphism. Bangladesh Journal of Anatomy July 2020, Vol. 18, No. 2, pp. 32-35